Heterogeneous Distributed Sensor Networks (HDSN) - Pathan, Al-Sakib Khan (Kyung Hee University, South Korea, 2007)
A new deployment model of distributed sensor network is presented where sensors with different functional types participate at the same time. In this model the sensors are associated with different deployment sets but they cooperate with each other within and out of their respective sets. We term this network model as Heterogeneous Distributed Sensor Network (HDSN). The heterogeneity here refers to the functional heterogeneity of the sensors participating in the network. The advantages of such network model and potential research scopes are also discussed.